(untitled) (International Journal of Physiotherapy, 2025)
Background: Pulmonary function is influenced by multiple factors, including age, gender, environmental exposure, and physical activity levels. While the roles of age and gender in determining lung health are well documented, the interplay between physical activity, geographical location, and pulmonary function in healthy individuals remains unexplored. Aim: This study examines the effects of geographical origin and physical activity levels on pulmonary function in healthy individuals. The primary objective is to understand how environmental variations in lifestyle factors contribute to lung performance and respiratory health. Methods: A total of 90 healthy participants from Delhi were recruited based on geographical origin and physical activity levels. Participants were divided into subgroups. Pulmonary functions were evaluated using spirometry, measuring forced vital capacity (FVC), forced expiratory volume in one second (FEV1), and (FEV1/FVC). Results: A significant positive correlation was observed between physical activity and pulmonary parameters, including FEV1 (r=0.425, p<0.001), FVC (r=0.470, p<0.001), and FEV1/FVC (r=0.325, p=0.002). Geographic origin demonstrated minimal impact, with only FEV1 showing a statistically significant difference (r=0.880, p<0.001). Conclusion: This study highlights the critical role of physical activity in improving pulmonary function, with geographical origin showing a relatively minor influence. These findings reinforce the importance of promoting physical connectivity and maintaining optimal respiratory health.